Mechanism of an arched basilar membrane in mammalian cochlea - Chan, Wei Xuan (2016)
The mammalian cochlea is a highly sensitive transducer which converts acoustic vibration into electrical signal. The acoustic vibration enters via the stapes and travels in the scala fluid along the cochlea from its basal to apical end. Prior to the acoustic-electrical conversion, the acoustic vibration is mapped onto the basilar membrane based on decreasing frequencies from base to apex. The variation of dynamic structural properties of the basilar membrane contributes to the frequency-mapping and sensitivity of the cochlea. The basilar membrane in most species of mammals, including humans, varies in width and thickness. However, in few species of mammals, such as gerbil, their basilar membranes are arched and have a resting radial tension. These mammals retain their cochlear sensitivity despite the lack of varying width and thickness in their basilar membrane. The present research analyses the mechanism of an arched basilar membrane in contributing to the sharp frequency tuning in a gerbil cochlea. The findings provide understanding of an arched membrane in mammalian cochlea and enables development for application of the cochlear mechanics in areas such as microfluidics and artificial cochlear development where limitations on the channel width are critical.